Is athletic performance affected following concussion? A systematic review and meta-analysis of literature - Clarke, A.; Middleton, K.; Daly, E.; Ryan, L.; Carey, D.; Pearce, A. J. (The Journal of Sport and Exercise Science, 2021)
Emerging research has studied in-game metrics of athletes after returning from concussion injury in an attempt to determine if performance is compromised. The aim of this meta-analysis was to quantify performance metrics in professional athletes prior to and following recovery from concussion. We conducted systematic literature searches in databases: PubMed, SCOPUS, and SPORTDiscus, between January 1990 to July 2020. Meta-analyses compared, first, pre-versus post-concussion performance within concussed athletes, and second, performance between concussed and non-concussed athletes. After thorough review, seven studies presenting pre-/post-concussion performance were retrieved. The quality of studies analysed were rated as moderate to good. Meta-analyses showed no within-group differences in performance variables in athletes following a concussion. Between group analyses showed significant differences between groups post-concussion for some variables (e.g.,scoring, contribution to scoring and blocks); however, pre-concussion comparisons between groups also revealed significant differences. Collectively, our data reports no changes in athlete performance when returning to competition after suffering a concussion injury. While athletic performance appears to be affected in some variables, the retrospective nature and quasi-experimental observational designs of the studiesmakesinterpretation difficult. However, despite study limitations, future research in this area should continue, as concussion in sport is not only a medical concern, but also a concern for high performance staff who are unsure how to work with post-concussed athletes following medical clearance to train and compete.